(untitled) - Dr. Aruna Deshpande (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Our country India is a culturally very religious and diverse, according to changing environmental and human needs this approach needs to adapt and improve on hygiene and inclusivity. We need to be inclusive and conscious of education due to the global connectivity. Appreciate the humans needed to work with dignity and respect. This is a case article is based on the lines of the awareness of sustainability and a social initiative brought about by a young Indian entrepreneur Mr. Ankit Agarwal and his Team of young educated members who started this initiative the Phool; which is based on the idea of using wasted flowers offered in temples, to create fragrances and other products and market it in the different parts of the country and also spread the market globally. This entrepreneurial social enterprise also took the initiative to employ diverse women and empower marginalised by hiring them, and making them economically stable to give them a life to live with dignity and respect. It is this oppression, which demotes millions to injustice and poverty, and in the Covid-19 Lockdown phase and been trying to tackle this social initiative in the dynamic environment. During the lockdown, the company ensured its supply chain by sourcing flower waste directly from the distressed horticulture farmers, bringing them critical income during times. Phool.co has given a life of dignity to dozens of women, and it did this despite having an option of automating the process.